The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.heliyon.2020.e05502
|View full text |Cite
|
Sign up to set email alerts
|

Do soil amendments used to improve agricultural productivity have consequences for soils contaminated with heavy metals?

Abstract: This study presents an analysis of the effects of manure and lime commonly used to improve agricultural productivity and evaluates the potential for such soil amendments to mobilise/immobilise metal fractions in soils contaminated from nearby mine tailings in the Zambian Copperbelt. Lime and manure were applied at the onset of the study, and their effects were studied over two planting seasons, i.e. 2016-17 and 2017-18. Operationally defined plant-available Cd, Cu, Ni, Pb and Zn in the soil, were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Metal elements may have different behaviors such as bioavailability, leachability, and mobility in various environments. An extractable form by DTPA is commonly applied to evaluate availability in previous many studies ( Kim et al, 2015 ; Zahedifar et al, 2017 ; Kaninga et al, 2020 ). It was reported that Cd and Cu were readily extracted by DTPA compared to Pb and Zn ( Singh et al, 1998 ), suggesting that Cd and Cu have more bioavailability in the same field condition, and therefore it should be possible to incur more leachability and/or mobility in a wet–dry cropping rotation due to the function of water.…”
Section: Discussionmentioning
confidence: 99%
“…Metal elements may have different behaviors such as bioavailability, leachability, and mobility in various environments. An extractable form by DTPA is commonly applied to evaluate availability in previous many studies ( Kim et al, 2015 ; Zahedifar et al, 2017 ; Kaninga et al, 2020 ). It was reported that Cd and Cu were readily extracted by DTPA compared to Pb and Zn ( Singh et al, 1998 ), suggesting that Cd and Cu have more bioavailability in the same field condition, and therefore it should be possible to incur more leachability and/or mobility in a wet–dry cropping rotation due to the function of water.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) Cd (0.98) Cu (29.6) Pb (3.34) Zn (38) Mining area Iran Cd (0.9) Shojaei et al. (2021) Cr (0.87) Mn (0.88) Pb (0.94) Mining area India Cd (5.16) Pradhan et al., 2020 Co (3,097.01) Cr (3,012.45) Cu (7.51) Fe (5,485.01) Mn (5,840.5) Ni (2,281.01) Zn (226.1) Mining area Zambia Cd (0.45) Kaninga et al. (2020) Cu (979) Ni (44) Pb (10.2) Zn (32) Mining area Morocco Cu (964.1) Raklami et al.…”
Section: Heavy Metal Contaminated Soil and Bioaugmentation Treatmentmentioning
confidence: 99%
“…Each sub-plot was 45 m 2 , consisting of six 10 m long ridges, spaced 90 cm apart. Soil samples were collected from each plot and characterized for basic soil fertility, and heavy metal concentrations before amendments were applied as detailed in Kaninga et al (2020b). Lime (CaCO 3 ) and pre-treated chicken manure (designated 'manure') were applied only within the ridge area, i.e.…”
Section: Study Site and Field Experimentationmentioning
confidence: 99%
“…For quality assurance, blanks, duplicates and certified reference materials (CRMs) including NIST 1573a (tomato leaves), NIST 1570a (spinach) and NIST 1567b (wheat flour) were analysed alongside the plant samples -the latter are presented in Supplementary Table 1 demonstrating good analytical performance. Soil chemistry data was reported in Kaninga et al (2020b). For this paper, only crop data is considered for exposure related to direct human consumption of food produce.…”
Section: Plant Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation